Formation and realization of the state political myth in Ukraine: trends and contradictions - Топалова, С. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The problems of formation and realization of the state political myth in Ukraine are explored in the article. The main factors that contribute to the intensification of public request for myth are identified. The article shows the features of the functioning of political parties, which hold back the process of designing and implementation of the state’s development strategy. It also determines the factors that affect the perspectives of Ukraine in accordance with the declared strategy of democratization and European integration.